2019
DOI: 10.1002/celc.201901063
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Signature of Escherichia coli on Nickel Micropillar Array Electrode for Early Biofilm Characterization

Abstract: Biofilms are sessile microbial communities living at interfaces, in which the extracellular matrix is responsible for the mechanical stability and adhesion to surfaces. Transition from planktonic to attached cells is a key step in the biofilm formation process. Monitoring of this transition is needed to prevent contamination of biomedical devices and mitigate microbially influenced corrosion. Under anoxic local conditions and in the presence of an exogenous redox mediator, biofilms can divert part of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Particular interest is always given to CV, since this method provides information about the formation of biofilms and their electrochemical and electro-catalytic activities, extracted from the realtime recording of voltammograms [81]. CV was used to characterize the anaerobic growth of E. coli and its secreted mediators and evaluate their role in the functioning of the cell, after the formation of a biofilm on the surface of the platinized titanium mesh electrodes [82]. Moreover, the biofilm formation and microbial adherence to the electrode surface could On the other hand, electrochemically inactive biofilms could be integrated with electrode surfaces via extracellular electron receptors/transmitters, or electron mediators.…”
Section: Half-cell Based Messmentioning
confidence: 99%
“…Particular interest is always given to CV, since this method provides information about the formation of biofilms and their electrochemical and electro-catalytic activities, extracted from the realtime recording of voltammograms [81]. CV was used to characterize the anaerobic growth of E. coli and its secreted mediators and evaluate their role in the functioning of the cell, after the formation of a biofilm on the surface of the platinized titanium mesh electrodes [82]. Moreover, the biofilm formation and microbial adherence to the electrode surface could On the other hand, electrochemically inactive biofilms could be integrated with electrode surfaces via extracellular electron receptors/transmitters, or electron mediators.…”
Section: Half-cell Based Messmentioning
confidence: 99%
“…The changes in impedance at the low frequency region of the EIS plots observed in the DFRT with two resistor-CPE circuits (Figure 3d) was chosen to represent the electrochemical 282 system, with one additional resistor in series to account for the resistance in the solution [55].…”
mentioning
confidence: 99%
“…For such studies, external redox mediators were often added to aid the EET. For example, addition of ferricyanide/ferrocyanide couple or HNQ to the electrolyte exhibited a change in the charge transfer characteristics at the E. coli coated electrode [215,241,242]. The aforementioned studies showed the competence of EIS to detect the adhesion of weakly electroactive bacteria at the electrode via changes in impedimetric parameters such as charge transfer resistance and double layer capacitance with or without redox probes.…”
Section: Monitoring Growth Development and Disruption Of P Aeruginosa Biofilms By Eismentioning
confidence: 96%
“…Previously, supplementing Enterococcus faecalis biofilms with iron promoted the EET thereby, increasing the electroactivity [214]. Similarly, addition of quinone derivatives such as anthraquinone-2,6-disulfonic acid and 2-hydroxy-1,4-naphthoquinone (HNQ) to Shewanella putrefaciens and E. coli respectively enhanced the EET activity [204,215].…”
Section: Extracellular Electron Transfer Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation